First successful transcatheter valve-in-valve implantation into a failed mechanical prosthetic aortic valve facilitated by fracturing of the leaflets: a case report. Issue 7 (30th July 2021) - Butter, Christian; Kühnel, Ralf-Uwe; Hölschermann, Frank
Abstract: Background: Degenerated and failed bioprosthetic cardiac valves can safely be treated with transcatheter valve-in-valve implantation in patients at high risk for reoperation. So far, non-functional mechanical valves must be treated with a surgical redo. Breaking the carbon leaflets before implanting a transcatheter valve into the remaining ring has never been described before. Case summary: Here, we present the case of a 65-year-old male patient with severe heart failure, poor left ventricular function based on a fully immobile disc of his mechanical bileaflet aortic valve implanted 7 years ago. After the heart team declined to reoperate the patient due to his extremely high risk, we considered a transcatheter valve-in-valve implantation as the ultimate treatment approach. After successful interventional cracking of the leaflets in vitro, this approach, together with implanting a balloon-expandable transcatheter aortic valve replacement (TAVR) into the remaining ring, was performed under cerebral protection. The intervention resulted in a fully functional TAVR, improvement of heart function, and early discharge from the hospital. Discussion: This case demonstrates the possibility to implant a transcatheter valve successfully into a non-functional mechanical bileaflet aortic prosthesis after fracturing the carbon discs while the brain is protected by a filter system. Critical steps of the procedure were identified. This new therapeutic approach might be offered to a limited patient cohort who is not eligible for a surgical redo.